Implementation of cooperatives' principles on ranked-cooperatives, East Java 2012 - Harwiki, Wiwiek; Surya Saputra, Ruswiati (International Foundation for Research & Development, 2014)
The purposes of this research are to identify values and cooperatives' principles on the field, to identify roles and member participation to improving cooperatives, to identify cooperatives' performance based on cooperatives' principles, and to identify problems in order to implementing the cooperatives' principles. Samples were collected at 52 cooperatives that have been assessed as the accredited cooperatives by small medium enterprise and cooperatives office in the East Java. Data have been analyzed and evaluated on two steps: grading the defined instrument and checking the supported documents given by respondents. To implement cooperatives' principles, there were correlations between management control and members' satisfaction, boards' performance and members' satisfaction, well-controlled administration and members' satisfaction, capital structure and members' satisfaction, unit business and members' satisfaction, training and education and members' satisfaction, cohesiveness and members' satisfaction.